2019
DOI: 10.3174/ajnr.a5953
|View full text |Cite
|
Sign up to set email alerts
|

Ostium Ratio and Neck Ratio Could Predict the Outcome of Sidewall Intracranial Aneurysms Treated with Flow Diverters

Abstract: Background and Purpose: To identify the potential for incomplete occlusion of intracranial aneurysms treated by flow-diverters (FD), we investigated if aneurysm ostium size in relation to parent artery size affects angiographic outcomes of FD-treated sidewall aneurysms. Materials and Methods: FD-treated sidewall aneurysms were divided into “occluded” and “residual” (incomplete occlusion) groups based on 6-month angiographic follow-up. We calculated ostium ratio (OsR), a new parameter defined as the aneurysm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…This prospective study compared geometric and hemodynamic parameters in unruptured sidewall intracranial aneurysms for different FD treatment responses at 2 follow-up time points. Other studies have reported on the parameters for differentiation of the aneurysm response, 15,16 but we highlighted the relationship between in vivo aneurysm hemodynamics and the treatment responses, and tried to give a hemodynamic explanation for the delayed occlusion. Our results showed geometric and hemodynamic differences between the occlusion and remnant groups at 6 and 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prospective study compared geometric and hemodynamic parameters in unruptured sidewall intracranial aneurysms for different FD treatment responses at 2 follow-up time points. Other studies have reported on the parameters for differentiation of the aneurysm response, 15,16 but we highlighted the relationship between in vivo aneurysm hemodynamics and the treatment responses, and tried to give a hemodynamic explanation for the delayed occlusion. Our results showed geometric and hemodynamic differences between the occlusion and remnant groups at 6 and 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Nevertheless, to our knowledge, few reports have investigated the relationship between the ostium and FD treatment response. 15,16 We hypothesized that different FD treatment responses were related to aneurysm features, and our study focused on the aneurysm geometries and hemodynamics at the ostium. The aim of this study was to perform an in vivo investigation of the relationship between aneurysm features, particularly the geometric and hemodynamic parameters and their impact on FD treatment responses.…”
mentioning
confidence: 99%
“…This means that a larger portion of the parent vessel was the opening into the aneurysms in this group, which allowed more flow into the aneurysmal sac. 40 In these cases, use of alternative strategies like overlapping FDs, compacted FD or FDs with adjunctive coils could be more beneficial for successful outcome, namely occlusion. 9,38 In the ideal case, our models will identify IAs that may not occlude with a single, uniformly implanted FD, promoting the interventionalist to consider these alternative methods.…”
Section: Discussionmentioning
confidence: 99%
“…All morphology parameters were previously defined,15 except for 3D neck ratio (NR 3D ), which we introduce in this study as the ratio of average neck dimension to average parent vessel diameter, both measured in 3D. It is a 3D version of our previously introduced two-dimensional (2D) neck ratio, NR 2D , which was found to be significantly associated with outcomes of flow diverter (FD)-treated IAs 16…”
Section: Methodsmentioning
confidence: 99%